2018
DOI: 10.18844/wjet.v10i2.3418
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of instructional videos

Abstract: Nowadays, video plays a significant role in education in terms of its integration into traditional classes, and is the principal delivery system of information in classes particularly in online courses as well as serving as a foundation for many blended classes. Hence, education is adopting a modern approach of instruction with the target of moving away from the traditional instructional approach to video-based learning (VBL). VBL is a powerful approach used in education in order to enhance learning results as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 0 publications
1
36
0
2
Order By: Relevance
“…Dong & Goh (2015) menjelaskan bahwa video yang layak dapat memberikan stimulis yang positif pada siswa meskipun pembelajaran dilakukan secara online ataupun mandir Dong & Goh (2015) explain that a good video can provide positive stimulation to students, even though learning is done online or independently [28]. On the other hand, Behehsti et al (2018) showed that activities supported by instructional videos enable active learning [29]. Although several studies also mentioned that video could be used as a useful tool in education [30].…”
Section: ) Validity Of the Video Tutorialmentioning
confidence: 99%
“…Dong & Goh (2015) menjelaskan bahwa video yang layak dapat memberikan stimulis yang positif pada siswa meskipun pembelajaran dilakukan secara online ataupun mandir Dong & Goh (2015) explain that a good video can provide positive stimulation to students, even though learning is done online or independently [28]. On the other hand, Behehsti et al (2018) showed that activities supported by instructional videos enable active learning [29]. Although several studies also mentioned that video could be used as a useful tool in education [30].…”
Section: ) Validity Of the Video Tutorialmentioning
confidence: 99%
“…The Organization is the only United Nations agency with a mandate to cover all aspects of education. It has been entrusted to lead the Global Education 2030 Agenda through Sustainable Development Goal four (4). The roadmap to achieve this is the Education 2030 Framework For Action (FFA).…”
Section: Educational Development Goal (Goal 4)mentioning
confidence: 99%
“…The use of video and media technologies has some positive aspects that contribute to improving the quality of education. In particular, in the process of training advertising specialists, the use of video materials provides ample opportunities for acquaintance with the achievements of modern practice (Behehsti et al, 2018;Vezne, 2020).…”
Section: Introductionmentioning
confidence: 99%